If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x) + -4(x) = 148 Multiply x * x 2x2 + -4(x) = 148 Reorder the terms: -4x + 2x2 = 148 Solving -4x + 2x2 = 148 Solving for variable 'x'. Reorder the terms: -148 + -4x + 2x2 = 148 + -148 Combine like terms: 148 + -148 = 0 -148 + -4x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-74 + -2x + x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-74 + -2x + x2)' equal to zero and attempt to solve: Simplifying -74 + -2x + x2 = 0 Solving -74 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '74' to each side of the equation. -74 + -2x + 74 + x2 = 0 + 74 Reorder the terms: -74 + 74 + -2x + x2 = 0 + 74 Combine like terms: -74 + 74 = 0 0 + -2x + x2 = 0 + 74 -2x + x2 = 0 + 74 Combine like terms: 0 + 74 = 74 -2x + x2 = 74 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 74 + 1 Reorder the terms: 1 + -2x + x2 = 74 + 1 Combine like terms: 74 + 1 = 75 1 + -2x + x2 = 75 Factor a perfect square on the left side: (x + -1)(x + -1) = 75 Calculate the square root of the right side: 8.660254038 Break this problem into two subproblems by setting (x + -1) equal to 8.660254038 and -8.660254038.Subproblem 1
x + -1 = 8.660254038 Simplifying x + -1 = 8.660254038 Reorder the terms: -1 + x = 8.660254038 Solving -1 + x = 8.660254038 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 8.660254038 + 1 Combine like terms: -1 + 1 = 0 0 + x = 8.660254038 + 1 x = 8.660254038 + 1 Combine like terms: 8.660254038 + 1 = 9.660254038 x = 9.660254038 Simplifying x = 9.660254038Subproblem 2
x + -1 = -8.660254038 Simplifying x + -1 = -8.660254038 Reorder the terms: -1 + x = -8.660254038 Solving -1 + x = -8.660254038 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -8.660254038 + 1 Combine like terms: -1 + 1 = 0 0 + x = -8.660254038 + 1 x = -8.660254038 + 1 Combine like terms: -8.660254038 + 1 = -7.660254038 x = -7.660254038 Simplifying x = -7.660254038Solution
The solution to the problem is based on the solutions from the subproblems. x = {9.660254038, -7.660254038}Solution
x = {9.660254038, -7.660254038}
| .25(2d+1)= | | 45j-6+1=108 | | 3x^2+7x=172 | | 5651.8116=2*3.14r^2+2*3.14*r*55.6 | | 5[3x-(-3-x)+2]=-4x-28 | | -3=3t-54 | | 5x-3x=13-5 | | (3x-35)+130=180 | | 0.5(-3a-7)-0.75(2a)=-a+7 | | 3w^3+21w^2+36w=0 | | x-(4)=15 | | (k-2)(7k-3)=0 | | 2-4=6 | | Cos^2x-1-sin^2x+sinx=0 | | 225+1=1+3x+1 | | 10-5=18 | | X^2-x+39=0 | | 2x+5y=2z | | 5p+38=-7(4+4p) | | 500-3a=200 | | a(a+1)=10 | | h=-9.8t+45t+1 | | 26=x-4 | | -6x+1=7(4x+5) | | 7y-6=15y+42 | | 3x^2-x-3=x^2 | | 12x-4x-9x^2=0 | | 0.7z=-105 | | 41+x-3=-13y | | -(3xy-11)+4(4xy+5)= | | x^5+30=273 | | 5x-8x+22=2x+27 |